ZrOx-Beta catalyst as well as preparation method and application thereof
By preparing ZrOx-Beta catalyst with high content of monoclinic phase zirconia, the problem of poor activity stability of existing catalysts is solved, and high selectivity and long operation time in butadiene conversion reaction are achieved.
Patent Information
- Application Number
- CN202311116986.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-31
AI Technical Summary
The existing Zr-Beta catalysts have poor activity stability, easy carbon accumulation, and short operation time in the butadiene conversion reaction.
By preparing a ZrOx-Beta catalyst with high content of monoclinic phase zirconia, a catalyst with excellent catalytic properties is formed by using methods such as acid-eluting aluminum, crystallization treatment and Zr-supporting.
It significantly improves the selectivity of butadiene and the conversion of raw materials, extends the operation time of the catalyst, and improves the activity stability.
Smart Images

Figure CN119524917A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalysts, and in particular to ZrO x -Beta catalyst and its preparation method and application of the catalyst in hydrocarbon conversion reaction. Background Art
[0002] Butadiene (1,3-Butadiene, BD) is an important petrochemical raw material and an intermediate monomer of synthetic rubber. It plays an important role in industrial production, especially in rubber production and the automobile industry. With the development of naphtha cracking technology to produce ethylene, about 97% of the world's butadiene is produced by extracting the by-product 1,3-butadiene from the carbon four fraction. However, with the increasing scarcity of oil resources and the continuous rise in oil prices, the process of producing butadiene using the oil route is bound to be affected. Therefore, it is urgently needed to develop a non-petroleum route for butadiene production. In recent years, with the continuous maturity of bioethanol production technology and the gradual increase in production scale, the ethanol method for preparing butadiene will be a new method to replace the petroleum route. There are two production processes for preparing butadiene (ETB) from ethanol: the one-step process (Makshina EV, Dusselier M, Janssens W, et al. Chemical Society Reviews, 2014, 43(22): 7917-7953.), which is the Lebedev process developed in the 1920s, using ethanol as a raw material to produce butadiene. This process has a low butadiene selectivity and a high acetaldehyde selectivity. The selectivity of butadiene is increased by recycling acetaldehyde to 30-40%; the two-step process (Alessandro M, Oberto C. Process for the manufacture of diolefins from alcohols and aldehydes. US2297424A.1942.; Dunn JT, Toussaint W J. Process for making diolefins. US2421361A[P].1947.), namely the Ostromyslensky process developed in 1942, partially dehydrogenates ethanol in the first reactor to produce acetaldehyde, and converts the ethanol-acetaldehyde mixture into butadiene in the second reactor, with a selectivity of up to 60%. Among them, the two-step process has more significant advantages.
[0003] Both the one-step and two-step processes include the following five reaction steps: ① ethanol dehydrogenation to generate acetaldehyde; ② acetaldehyde undergoes aldol condensation reaction to generate butane aldol; ③ butane aldol dehydration to generate crotonaldehyde; ④ crotonaldehyde and ethanol undergo MPV reaction to generate crotyl alcohol and acetaldehyde; ⑤ crotyl alcohol dehydration to generate butadiene. Among them, the catalyst for the dehydrogenation of ethanol to generate acetaldehyde is mostly Ag and Cu, which can meet the needs of industrial production. Regarding the requirements for the second step reaction in the two-step process, existing research results have shown that elements such as Ta, Zr, Zn and Mg can enter the molecular sieve framework or pores, showing L acid centers, which are active centers in aldol condensation and MPV reduction reactions (T.-W.Kim, J.-W.Kim, C.-U.Kim, Chem. Eng. J. 2015, 278, 217-223); Si-OH on the surface of SiO2, MWW and Beta molecular sieves behaves as weak B acid, which is the active center for dehydration reactions (M.Gao, H.Jiang, M.Zhang, Catal. Surveys Asia 2020, 1-8; VL Shushkevich, IIIvanova, E.Taarning, Green Chem. 17 (4) (2015) 2552–2559.; PI Kyriienko, OV Larina, SOSoloviev, SM Orlyk, S. Dzwigaj. Catal. Commun. 77 (2016) 123–126.; Minhua Zhang, etc. Microporous and Mesoporous Materials 326 (2021) 111359). Among them, the Zr-Beta catalyst containing metal zirconium with pure silicon beta molecular sieve as the carrier has a high butadiene selectivity, with a feedstock conversion rate of 43.2% and a butadiene selectivity of 73.9%. However, the activity stability of the catalyst is poor, it is easy to deposit carbon, and it only runs for a few hours. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a ZrO x -Beta catalyst and preparation method thereof, wherein the prepared catalyst contains a high content of monoclinic zirconium oxide, and the catalyst exhibits excellent catalytic performance in the reaction of preparing 1,3-butadiene from ethanol-acetaldehyde.
[0005] In order to achieve the above-mentioned object, the present invention firstly provides a ZrO x -A method for preparing a Beta catalyst, the method comprising:
[0006] (1) acid washing and dealuminization of H-Beta molecular sieve to obtain Si-Beta molecular sieve;
[0007] (2) mixing Si-Beta molecular sieve, template and water, and then performing crystallization treatment to obtain the Recry-Beta molecular sieve;
[0008] (3) In the presence of a precipitant, Zr is loaded onto the Recry-Beta molecular sieve, and then dried and calcined to obtain the ZrO x -Beta catalyst;
[0009] Wherein, the particle size of the H-Beta molecular sieve is less than 90 nm;
[0010] Wherein, the molar ratio of the template agent to the Si-Beta molecular sieve calculated as SiO2 is 0.08-0.25;
[0011] The load conditions include: temperature of 60-140°C and positive pressure;
[0012] The amount of the sedimentation agent used is such that the pH of the material after loading is greater than 7 and less than 13.
[0013] The second aspect of the present invention provides ZrO prepared by the method as described above. x -Beta catalyst.
[0014] A third aspect of the present invention provides a ZrO x -Beta catalyst, the catalyst comprising Beta molecular sieve and a zirconium-containing species supported on the Beta molecular sieve, wherein the zirconium-containing species is a monoclinic / tetragonal mixed phase;
[0015] Wherein, the monoclinic phase accounts for 50%-80% of the zirconium-containing species;
[0016] Wherein, the crystallinity of the catalyst is 30-60%.
[0017] A fourth aspect of the present invention provides the ZrO x -Beta catalyst is used in hydrocarbon conversion reaction, preferably in the reaction of preparing 1,3-butadiene from ethanol-acetaldehyde.
[0018] Zirconia ZrO2 crystals have three stable crystal phases, monoclinic (m), tetragonal (t) and cubic (c). The first two are mostly used in catalytic reactions. The Zr / O coordination environments of different crystal phases are obviously different: in the tetragonal phase, Zr 4+ The ion is eight-coordinated, O 2- The ion is four-coordinated; in the monoclinic phase, Zr 4+ The ion is seven-coordinated, O 2-The ions are tri-coordinated or tetra-coordinated [Y.Zhao et al.Catalysis Communications 3 (2002) 239–245]. This structural difference causes the two different crystal phases of ZrO2 to have different acidity and catalytic properties. The m-ZrO2 structure is rich in Zr-OH-Zr structure, while the t-ZrO2 structure is mainly Zr-O-Zr structure [Weizhen Li, Hua Huang, Hongjia Li, Wei Zhang, and Haichao Liu,, Langmuir 2008, 24, 8358-8366]. The ZrO x -Beta catalyst contains a higher content of m-ZrO2, which can improve butadiene selectivity and activity stability.
[0019] The ZrO x -Beta catalyst has a lower internal surface area S micro and micropore volume V micro , higher stacking pore volume V meso And a higher amount of weak acid can promote the interaction between Zr-OH on the monoclinic ZrO2 and Si-OH on the surface of the molecular sieve, producing more Zr-O-Si-OH structures, improving the activity and selectivity of the catalyst and extending the operating time of the catalyst.
[0020] The ZrO prepared by the method of the present invention x -Beta catalyst can be used in the reaction of ethanol-acetaldehyde to prepare 1,3-butadiene, and the catalyst exhibits excellent catalytic performance, significantly improving the conversion rate of raw materials, the selectivity of 1,3-butadiene and the stable operation time. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the XRD diagram of the catalysts prepared in Examples 1, 2 and 3 of the present invention and Comparative Examples 1 and 2;
[0022] Figure 2 is the zirconium oxide XRD diagram of the catalysts prepared in Examples 1, 2 and 3 of the present invention and Comparative Examples 1 and 3;
[0023] Figure 3 1 is an XPS graph of the catalysts prepared in Examples 1, 2 and 3 of the present invention and Comparative Examples 1 and 2;
[0024] Figure 4 It is the UV-vis graph of the catalysts prepared in Examples 1, 2 and 3 of the present invention and Comparative Examples 1 and 2;
[0025] Figure 5The catalysts prepared in Examples 1, 2 and 3 and Comparative Examples 1 and 2 of the present invention are 29 Si MAS NMR images;
[0026] Figure 6 NH3-TPD diagram of the catalysts prepared in Examples 1, 2 and 3 of the present invention and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] The technical terms in the present invention shall be understood according to their definitions if they are defined, and shall be understood according to their general meanings in the art if they are not defined.
[0029] In a first aspect, the present invention provides a ZrO x -A method for preparing a Beta catalyst, the method comprising:
[0030] (1) acid washing and dealuminization of H-Beta molecular sieve to obtain Si-Beta molecular sieve;
[0031] (2) mixing Si-Beta molecular sieve, template and water, and then performing crystallization treatment to obtain the Recry-Beta molecular sieve;
[0032] (3) In the presence of a precipitant, Zr is loaded onto the Recry-Beta molecular sieve, and then dried and calcined to obtain the ZrO x -Beta catalyst;
[0033] Wherein, the particle size of the H-Beta molecular sieve is less than 90 nm (for example, it can be 20, 30, 40, 50, 60, 70, 80, 90 nm or less and any range between any two values);
[0034] Wherein, the molar ratio of the template to the Si-Beta molecular sieve calculated as SiO2 is 0.08-0.25 (for example, it can be 0.08, 0.1, 0.12, 0.14, 0.15, 0.16, 0.17, 0.18, 0.2, 0.25 and any range between any two values, preferably 0.13-0.18);
[0035] The load conditions include: temperature of 60-140°C and positive pressure;
[0036] The amount of the sedimentation agent used is such that the pH of the material after loading is greater than 7 and less than 13.
[0037] Preferably, the particle size of the H-Beta molecular sieve is 20-50 nm.
[0038] In the present invention, the particle sizes of the molecular sieve and the catalyst can be measured by transmission electron microscopy.
[0039] The H-beta molecular sieve can be purchased commercially or prepared at home. The preparation method thereof can be found in patent CN1324762A, which is incorporated herein by reference in its entirety.
[0040] In a preferred embodiment of the present invention, a silicon source, an aluminum source and a template are mixed under alkaline conditions and then subjected to hydrothermal crystallization, drying, ammonium exchange and calcination to obtain an H-beta molecular sieve. There is no particular restriction on the order of ammonium exchange and calcination.
[0041] The alkaline condition can be provided by a common alkaline substance in the art, such as sodium hydroxide.
[0042] The silicon source may be a conventional silicon source in the art, such as silicon dioxide or silica gel.
[0043] Preferably, the aluminum source is selected from one or more of alkali metal (meta)aluminates (such as sodium metaaluminate), hydrated aluminum oxide, aluminum hydroxide, hydrated aluminum chloride, and pseudo-boehmite.
[0044] Preferably, the template has at least one of the structures shown in formula (1):
[0045]
[0046] Wherein, R1, R2, R3 and R4 are each independently selected from an alkyl group having 1 to 4 carbon atoms, preferably, R1, R2, R3 and R4 are each independently selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl, more preferably methyl or ethyl;
[0047] X - Including hydroxide ions or halogen anions.
[0048] Preferably, the template is tetramethylammonium hydroxide and / or tetraethylammonium hydroxide.
[0049] It should be understood that the hydrothermal crystallization is performed under water-containing conditions.
[0050] Preferably, the amounts of the components are such that, in molar terms, SiO2 / Al2O3 is 10-50 (e.g., 10, 20, 30, 40, 50, and any range between any two values), H2O / SiO2 is 5-8 (e.g., 5, 6, 7, 8, and any range between any two values), template / SiO2 is 0.05-0.15 (e.g., 0.05, 0.08, 0.1, 0.12, 0.15, and any range between any two values), OH - / SiO2 is 0.1-0.15 (for example, it can be 0.1, 0.11, 0.12, 0.13, 0.14, 0.15 and any range between any two values).
[0051] Preferably, the hydrothermal crystallization is maintained at 120-200°C and autogenous pressure for 5-120 hours, more preferably at 80-138°C (preferably 110-130°C) and autogenous pressure for 5-72 hours (preferably 16-32 hours), and then at 140-200°C (preferably 140-160°C) and autogenous pressure for 5-72 hours (preferably 36-56 hours).
[0052] The drying and ammonium exchange methods are conventional methods in the art and will not be described in detail herein. The calcination conditions may be, for example, a temperature of 500-600° C. and a time of 3-5 hours.
[0053] Preferably, the conditions for acid washing and aluminum removal are such that the mass content of silicon dioxide in the obtained Si-Beta molecular sieve is above 99.5%, for example, it can be 99.5, 99.6, 99.7, 99.8, 99.9wt% or above and any range between any two values, thereby reducing the impurity content of the catalyst.
[0054] Preferably, the conditions for pickling include: a temperature of 60-90° C., an acid selected from one or more of nitric acid, hydrochloric acid and sulfuric acid, and a concentration of the pickling solution of generally 1-15 mol / L. The number and time of acid exchange are determined according to the content of silicon dioxide (or aluminum oxide) in the molecular sieve during actual operation.
[0055] The material obtained after acid washing can be subsequently treated to obtain the Si-Beta molecular sieve. The subsequent treatment operations may include filtering, washing and drying, etc., which can all refer to conventional operations in the art.
[0056] Preferably, the crystallinity of the Si-Beta molecular sieve is 60-90%, such as 60, 65, 70, 75, 80, 85, 90% and any range between any two values, more preferably 70-85%.
[0057] The crystallinity is measured by XRD, which is calculated as the sum of the characteristic peak areas of 2θ=7-9° and 22-23°, and the standard sample is the H-beta molecular sieve prepared in Preparation Example 1 of the present invention.
[0058] Preferably, the BET specific surface area S of the Si-Beta molecular sieve is BET 450-680m 2 / g, for example, 450, 480, 500, 550, 600, 650, 680m 2 / g and any range between any two values, more preferably 480-650m 2 / g.
[0059] Preferably, the total pore volume V of the Si-Beta molecular sieve is 总 0.25-0.85cm 3 / g, for example, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.85 cm 3 / g and any range between any two values, more preferably 0.45-0.7cm 3 / g.
[0060] Preferably, the stacking pore volume V of the Si-Beta molecular sieve is meso 0.2-0.55cm 3 / g, for example, 0.23, 0.25, 0.3, 0.4, 0.5, 0.55 cm 3 / g and any range between any two values, more preferably 0.26-0.48cm 3 / g.
[0061] Among them, specific surface area, pore volume and pore capacity can be measured by nitrogen adsorption instrument.
[0062] Preferably, the molar ratio of the template to the Si-Beta molecular sieve calculated as SiO2 is 0.1-0.2 (for example, it can be 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, and any range between any two values). The template is referred to as the template for preparing the H-beta molecular sieve, which will not be described in detail here.
[0063] Preferably, the molar ratio of water to Si-Beta molecular sieve calculated as SiO2 is 3-10, such as 3, 4, 6, 8, 10 and any range between any two values, more preferably 5-8.
[0064] Preferably, the crystallization conditions include: a crystallization temperature of 100-300° C., more preferably 110-150° C.; a crystallization time of 12 h-120 h, more preferably 24 h-72 h. It should be understood that the pressure is autogenous pressure.
[0065] Preferably, the crystallization is carried out in two steps, more preferably, crystallization is carried out at 110-130° C. for 18-36 h, and then crystallization is carried out at 130-150° C. for 18-36 h.
[0066] Preferably, the calcination conditions include: a calcination temperature of 400-650° C., more preferably 500-600° C.; and a calcination time of 2-8 h, preferably 3 h-5 h.
[0067] The Recry-Beta molecular sieve preparation method can be cited from Patent 202310644040.9, which is incorporated herein by reference in its entirety.
[0068] In the present invention, Zr is loaded onto the Recry-Beta molecular sieve, and then dried and calcined to obtain the ZrOx-Beta catalyst.
[0069] The Zr can be loaded onto the prepared Recry-Beta molecular sieve by, for example, an impregnation method (i.e., an equal volume impregnation method) or an ion exchange method. The preparation method can be to contact a Zr precursor solution with the Recry-Beta molecular sieve, wherein the Zr can be a water-soluble compound and an alcohol-soluble compound of Zr, such as one or more of nitrate (e.g., ZrO(NO3)2·2H2O), chloride and acetate.
[0070] In addition, the amount of solvent in the solution of the Zr precursor should satisfy the requirement that the Zr precursor can be fully dissolved in the solvent on the one hand, and the molecular sieve should be fully dispersed on the other hand. Preferably, compared with 1g of Recry-Beta molecular sieve, the amount of solvent in the solution of the Zr precursor is 5-100g, for example, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100g and any range between any two values, more preferably 10-50g. Wherein, the solvent can be at least one of water, ethanol and propanol.
[0071] Wherein, the load conditions include: a temperature of 60-140°C (for example, 60, 70, 80, 90, 100, 110, 120, 130, 140°C and any range between any two values, more preferably 80-120°C).
[0072] In step (3), the amount of the sedimentation agent is such that the pH of the material after loading is greater than 7 and less than 13, for example, it can be 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, and any range between any two values, more preferably 8 to 12. The pH of the material after loading can be the pH value directly measured after opening the reaction vessel after the reaction is completed.
[0073] Preferably, the sedimentation agent is selected from at least one of urea, ammonia and ammonium salts (such as ammonium chloride, ammonium sulfate, ammonium nitrate, ammonium bicarbonate, etc.).
[0074] Among them, the load conditions also include: the pressure is positive pressure, the pressure can be self-generated pressure, that is, the loading process is carried out in a closed container, or it can be external pressure, for example, the pressure value can be above 0.1MPa, 0.11MPa, 0.12MPa, 0.13MPa, 0.14MPa, 0.15MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa and any range between any two values, preferably 0.2-0.8MPa.
[0075] Preferably, the load condition also includes: a time of 4-68 hours, such as 4, 6, 8, 10, 15, 20, 25, 30, 40, 50, 60, 68 hours and any range between any two values, preferably 10-50 hours.
[0076] There is no particular restriction on the drying conditions, for example, the drying can be carried out at 60-120° C. There is no particular restriction on the drying time, as long as the drying is carried out until the weight is constant.
[0077] Preferably, the calcination conditions include: a temperature of 400-600° C. and a time of 1-6 hours.
[0078] Preferably, the amount of each component is such that, based on the total weight of the catalyst, the content of Recry-Beta molecular sieve is 95-99.9wt%, such as 95, 96, 97, 98, 99, 99.5, 99.9wt% and any range between any two values, more preferably 97-99.5wt%, and the content of zirconium-containing species calculated as Zr oxide is 0.1-5wt%, such as 0.1, 0.5, 1, 2, 3, 4, 5wt% and any range between any two values, more preferably 0.5-3wt%.
[0079] The second aspect of the present invention provides ZrO prepared by the method as described above. x -Beta catalyst.
[0080] Preferably, the zirconium-containing species in the catalyst is a monoclinic / tetragonal mixed phase, wherein the proportion of the monoclinic phase in the zirconium-containing species is more than 50%, for example, it can be 50, 55, 60, 65, 70, 75, 80, 90% or more and any range between any two values, more preferably 55-80%.
[0081] The proportion of monoclinic phase in zirconium-containing species is calculated as the ratio of monoclinic peak area to (monoclinic + tetragonal) peak area in the XRD spectrum of zirconium oxide.
[0082] The proportion of monoclinic phase,
[0083] The proportion of the four phases,
[0084] The area refers to the peak area of the peak corresponding to the 2θ value, such as S 2θ=24.2 It refers to the peak area of the peak when 2θ is 24.2.
[0085] Preferably, the crystallinity of the catalyst is 20-60%, for example, it can be 20, 25, 30, 35, 40, 45, 50, 60% and any range between any two values, preferably 30-65%. The crystallinity of the catalyst is analyzed by XRD, with the sum of the characteristic peak areas of 2θ=7-9° / 22-23° of the H-Beta molecular sieve prepared in Preparation Example 1 of Patent 202310644040.9 as the benchmark.
[0086] Preferably, based on the total weight of the catalyst, the content of Recry-Beta molecular sieve is 95-99.9wt%, such as 95, 96, 97, 98, 99, 99.5, 99.9wt% and any range between any two values, more preferably 97-99.5wt%, and the content of zirconium-containing species calculated as Zr oxide is 0.1-5wt%, such as 0.1, 0.5, 1, 2, 3, 4, 5wt% and any range between any two values, more preferably 0.5-3wt%.
[0087] Preferably, the silicon-to-aluminum ratio of the catalyst is above 800, for example, it can be 800, 1000, 1500, 2000, 2500 or above and any range between any two values, more preferably 1200-2500.
[0088] Preferably, the total acid content of the catalyst is 220-400 μmol / g, such as 220, 240, 260, 280, 300, 320, 340, 360, 380, 400 μmol / g and any range between any two values, preferably 250-350 μmol / g.
[0089] Preferably, in the catalyst, the ratio of weak acid to medium-strong acid is 2-7, such as 2, 3, 4, 5, 6, 7 and any range between any two values, preferably 3.5-6.5.
[0090] Preferably, the BET specific surface area S of the catalyst is BET 150-550m 2 / g, for example, 150, 200, 250, 300, 400, 450, 480, 500, 550 m 2 / g and any range between any two values, preferably 330-510m 2 / g.
[0091] Preferably, the total pore volume V of the catalyst is 总 0.45-0.7cm 3 / g, for example, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7 cm 3 / g and any range between any two values, preferably 0.55-0.67cm 3 / g.
[0092] Preferably, the catalyst has a stacked pore volume V meso 0.3-0.7cm 3 / g, for example, 0.3, 0.4, 0.5, 0.6, 0.7 cm 3 / g and any range between any two values, preferably 0.4-0.55cm 3 / g.
[0093] Preferably, the average particle size of the catalyst is 20-50 nm, preferably 20-30 nm.
[0094] A third aspect of the present invention provides a ZrO x -Beta catalyst, the catalyst comprising a molecular sieve and a zirconium-containing species supported on the molecular sieve, wherein the zirconium-containing species is a monoclinic / tetragonal mixed phase;
[0095] Wherein, the monoclinic phase accounts for more than 50% of the zirconium-containing species;
[0096] Wherein, the crystallinity of the catalyst is 30-60%.
[0097] Preferably, based on the total weight of the catalyst, the content of Recry-Beta molecular sieve is 95-99.9wt%, such as 95, 96, 97, 98, 99, 99.5, 99.9wt% and any range between any two values, more preferably 97-99.5wt%, and the content of zirconium-containing species calculated as Zr oxide is 0.1-5wt%, such as 0.1, 0.5, 1, 2, 3, 4, 5wt% and any range between any two values, more preferably 0.5-3wt%.
[0098] Preferably, the catalyst has a silicon to aluminum ratio of 1200-2500;
[0099] Preferably, the total acid amount of the catalyst is 250-350 μmol / g.
[0100] Preferably, in the catalyst, the ratio of weak acid to medium-strong acid is 3.5-6.5.
[0101] Preferably, the BET specific surface area S of the catalyst is BET 330-510m 2 / g.
[0102] Preferably, the total pore volume V of the catalyst is 总 0.55-0.67cm 3 / g.
[0103] Preferably, the catalyst has a stacked pore volume V meso 0.45-0.55cm 3 / g.
[0104] Preferably, the average particle size of the catalyst is 20-30 nm.
[0105] A fourth aspect of the present invention provides the ZrO x -Beta catalyst is used in hydrocarbon conversion reaction, preferably in the reaction of preparing 1,3-butadiene from ethanol-acetaldehyde.
[0106] The conditions for preparing 1,3-butadiene can be carried out with reference to the prior art, and are based on the ability to prepare 1,3-butadiene from ethanol-acetaldehyde.
[0107] According to the present invention, the conditions for the contact reaction of ethanol and acetaldehyde generally include reaction temperature and reaction pressure, wherein the reaction temperature can be maintained at 250-450°C, preferably 250-400°C; the reaction pressure can be maintained at 0.1-4MPa, preferably 0.1-1.5MPa. As long as the catalyst described in the present invention is used, the purpose of the present invention can be achieved. From the perspective of further improving the catalytic activity of the catalyst, the amount of the catalyst is set based on the total amount of ethanol and acetaldehyde so that the gas hourly space velocity of the reactants is 0.1-9 hours. -1 (h -1 ), preferably 0.1-6 hours -1 (h -1 ). The molar ratio of ethanol to acetaldehyde in the feed may be 1-12, preferably 1.5-5.
[0108] In the method of the present invention, the reaction of preparing 1,3-butadiene from ethanol can be carried out in various reactors conventionally used in the art, for example, including but not limited to at least one of a fixed bubbling bed reactor, a fixed trickle bed reactor and a slurry bed reactor.
[0109] The present invention will be described in detail below through examples.
[0110] (1) In the following examples, the crystallinity of the molecular sieve and the catalyst was analyzed by XRD, with the sum of the characteristic peak areas of 2θ=7-9° / 22-23° of the H-Beta molecular sieve prepared in Preparation Example 1 of Patent 202310644040.9 as the benchmark.
[0111] (2) In the following examples, the zirconium oxide content in the catalyst was measured according to the following analytical method: using a 3013 X-ray fluorescence spectrometer from Rigaku Corporation, Japan, under the following test conditions: tungsten target, excitation voltage 40 kV, excitation current 50 mA. Experimental process: The catalyst sample was pressed into a tablet and mounted on the X-ray fluorescence spectrometer, and emitted fluorescence under the irradiation of X-rays. The fluorescence wavelength λ and the atomic number Z of the element have the following relationship: λ=K(Z-S) -2 , K is a constant. As long as the wavelength λ of the fluorescence is measured, the element can be determined. The intensity of the characteristic spectral line of each element is measured with a scintillation counter and a proportional counter to perform quantitative or semi-quantitative analysis of the element.
[0112] (3) In the following examples, the total acid content, weak acid content and medium-strong acid content of the catalyst were measured according to the following method: AutochemⅡ2920 adsorption instrument produced by Micromeritic was used. A 20-40 mesh sample was loaded into a sample glass tube, and the glass tube was installed in a heating box. Helium was heated to remove surface impurities and then cooled to adsorb ammonia-helium. Then, helium was switched to heat and purge until ammonia was desorbed. The change of ammonia concentration was detected by a detector to obtain the NH3 adsorption-desorption curve, and the total acid content was obtained by automatic integration.
[0113] (4) In the following examples, the specific surface area and pore volume of the molecular sieve and catalyst were measured according to the following analytical methods:
[0114] Equipment: Micromeritic ASAP2010 static nitrogen adsorption instrument.
[0115] Measurement conditions: The sample was placed in a sample handling system and vacuumed to 1.33×10 -2 Pa, keep the temperature and pressure for 15 hours, and purify the sample. At liquid nitrogen temperature -196 ° C, measure the adsorption and desorption of nitrogen by the purified sample under different pressure ratios P / P0 to obtain the adsorption-desorption isotherm curve. Then use the two-parameter BET formula to calculate the total specific surface area, and the total pore volume is calculated based on the adsorption at P / P0 = 0.98.
[0116] In the following examples, all reagents and raw materials can be purchased commercially or prepared according to existing methods.
[0117] Citing the preparation method of Recry-Beta molecular sieve described in Preparation Example 3 of Patent 202310644040.9, Recry-Beta molecular sieve was prepared as ZrO x -Beta catalyst support.
[0118] Example 1
[0119] This example is used to illustrate the preparation method of the catalyst described in the present invention.
[0120] Take 4.0g of Recry-Beta molecular sieve, mix it with 60mL of aqueous solution containing 0.435g of ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add urea, transfer the above synthetic solution to a reactor with a polytetrafluoroethylene liner and seal it, and react it at 90°C for 20 hours, wherein the amount of urea added makes the pH value of the reaction solution 10 after the reaction. After washing the reaction solution with deionized water 3 times, place the filter cake in 100°C air to dry until all the water evaporates, and finally roast it in flowing air at 550°C for 2h to obtain a catalyst. In the catalyst, the content of Beta molecular sieve is 97.6%, and the content of zirconium dioxide is 1.76wt%.
[0121] Its XRD pattern is as follows Figure 1 As shown, the crystallinity of the catalyst is 54.8%, and the XRD pattern of zirconium oxide is as follows Figure 2 As shown in the figure, it can be seen that the catalyst contains monoclinic and tetragonal mixed phase zirconium oxide. The XPS graph is as follows Figure 3 As shown, the UV-Vis image is Figure 4 As shown, 29 Si MAS NMR images Figure 5 As shown in the figure, it can be seen that most of the metals enter the molecular sieve framework and form Zr-O-Si bonds and Zr-OH bonds with the framework elements. The NH3-TPD diagram is shown in Figure 6 shown.
[0122] The results of the crystallinity, zirconium dioxide content and acid amount of the product are shown in Table 1, and the results of the surface area and pore volume are shown in Table 2.
[0123] Example 2
[0124] This example is used to illustrate the preparation method of the catalyst described in the present invention.
[0125] Take 4.0g of Recry-Beta molecular sieve, mix it with 60mL of aqueous solution containing 0.435g of ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add urea, transfer the above synthetic solution to a reactor with a polytetrafluoroethylene liner and seal it, and react it at 90°C for 48 hours, wherein the amount of urea added makes the pH value of the reaction solution 11 after the reaction. After washing the reaction solution with deionized water 3 times, place the filter cake in 100°C air to dry until all the water evaporates, and finally roast it in flowing air at 550°C for 2h to obtain a catalyst. In the catalyst, the content of Beta molecular sieve is 97.2%, and the content of zirconium dioxide is 1.83wt%.
[0126] Its XRD pattern is as follows Figure 1As shown, the crystallinity of the catalyst is 33.1%, and the XRD pattern of zirconium oxide is as follows Figure 2 As shown in the figure, it can be seen that the catalyst contains monoclinic and tetragonal mixed phase zirconium oxide. The XPS graph is as follows Figure 3 As shown, the UV-Vis image is Figure 4 As shown, 29 Si MAS NMR images Figure 5 As shown in the figure, it can be seen that most of the metals enter the molecular sieve framework and form Zr-O-Si bonds and Zr-OH bonds with the framework elements. The NH3-TPD diagram is shown in Figure 6 shown.
[0127] The results of the crystallinity, zirconium dioxide content and acid amount of the product are shown in Table 1, and the results of the surface area and pore volume are shown in Table 2.
[0128] Example 3
[0129] This example is used to illustrate the preparation method of the catalyst described in the present invention.
[0130] Take 4.0g of Recry-Beta molecular sieve, mix it with 60mL of aqueous solution containing 0.435g of ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add urea, transfer the above synthetic solution to a reactor with a polytetrafluoroethylene liner and seal it, and react it at 90°C for 6 hours, wherein the amount of urea added makes the pH value of the reaction solution 9 after the reaction. After washing the reaction solution with deionized water 3 times, place the filter cake in 100°C air to dry until all the water evaporates, and finally roast it in flowing air at 550°C for 2h to obtain a catalyst. In the catalyst, the content of Beta molecular sieve is 97.8%, and the content of zirconium dioxide is 1.54wt%.
[0131] Its XRD pattern is as follows Figure 1 As shown, the crystallinity of the catalyst is 58.9%, and the XRD pattern of zirconium oxide is as follows Figure 2 As shown in the figure, it can be seen that the catalyst contains pure phase monoclinic zirconium oxide, and the XPS graph is as follows Figure 3 As shown, the UV-Vis image is Figure 4 As shown, 29 SiMAS NMR images Figure 5 As shown in the figure, it can be seen that most of the metals enter the molecular sieve framework and form Zr-O-Si bonds and Zr-OH bonds with the framework elements. The NH3-TPD diagram is shown in Figure 6 shown.
[0132] The results of the crystallinity, zirconium dioxide content and acid amount of the product are shown in Table 1, and the results of the surface area and pore volume are shown in Table 2.
[0133] Example 4
[0134] This example is used to illustrate the preparation method of the catalyst described in the present invention.
[0135] Take 4.0g Recry-Beta molecular sieve, mix it with 60mL aqueous solution containing 0.435g ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add urea, transfer the above synthetic solution to a reactor with a polytetrafluoroethylene liner and seal it, and react it at 90℃ for 72 hours. The amount of urea added makes the pH value of the reaction solution 12 after the reaction. After washing the reaction solution with deionized water for 3 times, place the filter cake in 100℃ air to dry until all the water evaporates, and finally roast it in flowing air at 550℃ for 2h to obtain a catalyst. Its XRD results show that the crystallinity of the catalyst is 23.5%.
[0136] Example 5
[0137] This example is used to illustrate the preparation method of the catalyst described in the present invention.
[0138] Take 4.0g Recry-Beta molecular sieve, mix it with 60mL aqueous solution containing 0.435g ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add urea, transfer the above synthetic solution to a reactor with a polytetrafluoroethylene liner and seal it, and react it at 120℃ for 20 hours. The amount of urea added makes the pH value of the reaction solution 11 after the reaction. After washing the reaction solution with deionized water for 3 times, place the filter cake in 100℃ air to dry until all the water evaporates, and finally roast it in flowing air at 550℃ for 2h to obtain a catalyst. Its XRD results show that the crystallinity of the catalyst is 50.1%.
[0139] Example 6
[0140] This example is used to illustrate the preparation method of the catalyst described in the present invention.
[0141] Take 4.0g of Recry-Beta molecular sieve, mix it with 60mL of aqueous solution containing 0.435g of ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add urea, transfer the above synthetic solution to a reactor with a polytetrafluoroethylene liner and seal it, and react it at 90°C for 20 hours. The amount of urea added is such that the pH value of the reaction solution after the reaction is 9. After washing the reaction solution with deionized water three times, place the filter cake in 100°C air to dry until all the water evaporates, and finally roast it in flowing air at 550°C for 2h to obtain a catalyst. The crystallinity of the catalyst is 56.4%.
[0142] Example 7
[0143] This example is used to illustrate the preparation method of the catalyst described in the present invention.
[0144] Take 4.0g of Recry-Beta molecular sieve, mix it with 60mL of aqueous solution containing 0.435g of ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add urea, transfer the above synthetic solution to a reactor with a polytetrafluoroethylene liner and seal it, and react it at 90°C for 20 hours. The amount of urea added is such that the pH value of the reaction solution is 8 after the reaction. After washing the reaction solution with deionized water three times, place the filter cake in 100°C air to dry until all the water evaporates, and finally roast it in flowing air at 550°C for 2h to obtain a catalyst. The crystallinity of the catalyst is 58.3%.
[0145] Example 8
[0146] This example is used to illustrate the preparation method of the catalyst described in the present invention.
[0147] Take 4.0g of Recry-Beta molecular sieve, mix it with 60mL of aqueous solution containing 0.435g of ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add urea, transfer the above synthetic solution to a reactor with a polytetrafluoroethylene liner and seal it, react at 90°C for 20 hours, wherein the amount of urea added makes the pH value of the reaction solution 12 after the reaction. After washing the reaction solution with deionized water three times, place the filter cake in 100°C air to dry until all the water evaporates, and finally roast it in flowing air at 550°C for 2h to obtain a catalyst. The crystallinity of the catalyst is 35.6%.
[0148] Example 9
[0149] This example is used to illustrate the preparation method of the catalyst described in the present invention.
[0150] Take 4.0g of Recry-Beta molecular sieve, mix it with 120mL of ethanol containing 0.435g of ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add ammonia water, transfer the above synthetic liquid to a reactor with a polytetrafluoroethylene liner and seal it, react at 80°C for 3 hours, wherein the amount of ammonia water added makes the pH value of the reaction liquid 8 after the reaction. After washing the reaction liquid with deionized water 3 times, place the suspension in 100°C air to dry until all the water evaporates, and finally roast it in flowing air at 550°C for 2h to obtain a catalyst. The crystallinity of the catalyst is 60.3%.
[0151] Comparative Example 1
[0152] This comparative example is used to illustrate the preparation method of a reference catalyst.
[0153] Take 4.0g of Recry-Beta molecular sieve, mix it with 120mL of aqueous solution containing 0.435g of ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add urea, and continue stirring in a three-necked flask at 90°C for 6 hours to end the reaction, wherein the amount of urea added is such that the pH value of the reaction liquid after the reaction is completed is 7. The suspension is placed in air at 100°C and dried until all water evaporates, and finally calcined in flowing air at 550°C for 5h to obtain a catalyst. In the catalyst, the content of Beta molecular sieve is 97.9%, and the content of zirconium dioxide is 1.47wt%.
[0154] Its XRD pattern is as follows Figure 1 As shown, the crystallinity of the catalyst is 60.9%, and the XRD pattern of zirconium oxide is as follows Figure 2 As shown in the figure, it can be seen that the catalyst contains monoclinic and tetragonal mixed phase zirconium oxide. The XPS graph is as follows Figure 3 As shown, the UV-Vis image is Figure 4 As shown, 29 Si MAS NMR images Figure 5 As shown in the figure, it can be seen that most of the metals enter the molecular sieve framework and form Zr-O-Si bonds and Zr-OH bonds with the framework elements. The NH3-TPD diagram is shown in Figure 6 shown.
[0155] The results of the crystallinity, zirconium dioxide content and acid amount of the product are shown in Table 1, and the results of the surface area and pore volume are shown in Table 2.
[0156] Comparative Example 2
[0157] This comparative example is used to illustrate the preparation method of a reference catalyst.
[0158] Take 4.0g of Recry-Beta molecular sieve, mix it with 60mL of aqueous solution containing 0.435g of ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add urea, transfer the above synthetic solution to a reactor with a polytetrafluoroethylene liner and seal it, react at 150°C for 20 hours, wherein the amount of urea added makes the pH value of the reaction solution 13 after the reaction. After washing the reaction solution with deionized water 3 times, place the filter cake in 100°C air to dry until all the water evaporates, and finally roast it in flowing air at 550°C for 2h to obtain a catalyst. In the catalyst, the content of Beta molecular sieve is 97.0%, and the content of zirconium dioxide is 1.89wt%.
[0159] Its XRD pattern is as follows Figure 1 As shown, the catalyst is amorphous, and the XPS diagram is as follows Figure 3 As shown, the UV-Vis image is Figure 4 As shown, 29 Si MAS NMR images Figure 5 As shown in the figure, it can be seen that most of the metals enter the molecular sieve framework and form Zr-O-Si bonds and Zr-OH bonds with the framework elements. The NH3-TPD diagram is shown in Figure 6 shown.
[0160] The results of the crystallinity, zirconium dioxide content and acid amount of the product are shown in Table 1, and the results of the surface area and pore volume are shown in Table 2.
[0161] Comparative Example 3
[0162] This comparative example is used to illustrate the preparation of a comparative catalyst.
[0163] Take 4.0g Recry-Beta molecular sieve and mix it with 120mL ethanol solution containing 0.435g ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, and stir it continuously for 3 hours at 80℃. After the reaction, the pH value of the reaction liquid is 7. The suspension is placed in air at 100℃ and dried until all ethanol evaporates, and finally calcined in flowing air at 550℃ for 2h to obtain a catalyst. In the catalyst, the crystallinity of Beta molecular sieve is 73.8%. The XRD pattern of zirconium oxide is as follows Figure 2 As shown, it can be seen from the figure that the catalyst contains pure phase tetragonal zirconia.
[0164] The results of the crystallinity, zirconium dioxide content and acid amount of the product are shown in Table 1, and the results of the surface area and pore volume are shown in Table 2.
[0165] Comparative Example 4
[0166] This comparative example is used to illustrate the preparation of a comparative catalyst.
[0167] Take 4.0g Recry-Beta molecular sieve, mix it with 60mL aqueous solution containing 0.435g ZrO(NO3)2·2H2O (AcrosOrganic, 99.99%) at room temperature, add urea, transfer the above synthetic solution to a reactor with a polytetrafluoroethylene liner and seal it, and react it at 90℃ for 20 hours. The amount of urea added makes the pH value of the reaction solution 13 after the reaction. After washing the reaction solution with deionized water for 3 times, place the filter cake in 100℃ air to dry until all the water evaporates, and finally roast it in flowing air at 550℃ for 2h to obtain the catalyst. Its XRD results show that the catalyst is amorphous.
[0168] Table 1
[0169]
[0170] It can be seen from the results in Table 1 that with the increase of preparation temperature and the extension of time, the monoclinic zirconia of the catalyst further increases, the crystallinity gradually decreases, the zirconia content gradually increases, and the weak acid amount and weak acid ratio gradually increase, indicating that monoclinic zirconia is more able to interact with the Beta molecular sieve carrier.
[0171] Table 2
[0172]
[0173]
[0174] From the results in Table 2, it can be seen that compared with Recry-Beta molecular sieve, the BET specific surface area S BET and micropore volume V micro The accumulation pore volume V meso The accumulation pore volume V of the catalysts increased slightly, except for catalyst 1. meso The increase indicates that the zirconium species has entered the pores or framework of the molecular sieve.
[0175] Test Example 1
[0176] The fixed bed reactor is used to prepare 1,3-butadiene from ethanol. The reactor is a stainless steel tubular isothermal reaction tube with an inner diameter of 12 mm and a catalyst loading of 4 g. Ethanol and acetaldehyde (the concentration of acetaldehyde aqueous solution is 40 wt%) are introduced from the top of the reaction tube. The device is material balanced and the liquid recovery is more than 95%.
[0177] Evaluation conditions: based on a mixture of ethanol and acetaldehyde as reactants, gas hourly space velocity: 2h -1; Carrier gas flow rate: 450ml / min, reaction temperature: 350℃, reaction pressure: 0.44MPa, catalyst loading: 2.0g. Ethanol and acetaldehyde solution are used as raw materials, wherein ethanol: acetaldehyde = 1:1 (molar ratio).
[0178] For the convenience of expression, the following substances are abbreviated as: ethanol (EtOH), acetaldehyde (AA), unreacted ethanol (unreacted-EtOH), and unreacted acetaldehyde (unreacted-AA).
[0179] The ethanol conversion and 1,3-butadiene selectivity were calculated by the following formula:
[0180]
[0181]
[0182] Wherein, n is the mass percentage of each component in the product, and i is butadiene or other components in the product.
[0183] The catalysts prepared in the examples and comparative examples were respectively used in the reaction of ethanol-acetaldehyde to prepare 1,3-butadiene. The catalytic performance results are shown in Table 3 (sampling results when the reaction time is 2 h, and the operating time is the time when the butadiene selectivity is greater than 60%).
[0184] Table 3
[0185]
[0186] It can be seen from the results in Table 3 that the ZrO prepared by the method of the present invention x When the -Beta catalyst is used in the reaction of preparing 1,3-butadiene from ethanol, the conversion rate of ethanol-acetaldehyde is high, and the butadiene selectivity, yield and operation time are significantly better than those of the comparative example. This shows that the catalyst provided by the present invention has good catalytic performance.
[0187] from Figure 2-6 The results show that, compared with Comparative Examples 1 and 2, the catalysts prepared in Examples 1 and 2 contain active components with a high content of monoclinic zirconium oxide, so that most of the metals enter the molecular sieve framework and form bonds with the framework elements, thereby improving the activity and selectivity of the catalyst and effectively extending the stable operation time (can continuously operate for at least 91 hours when the ethanol-acetaldehyde conversion rate is above 40% and the butadiene selectivity is ≥60%). The catalysts prepared in Comparative Examples 1 and 2 can only continuously operate for less than 30 hours when the butadiene selectivity is ≥60%, and have poor repeatability and decay quickly.
[0188] According to the method described above, the catalyst described in Example 1 of the present invention was used to prepare 1,3-butadiene under the condition of an alcohol-aldehyde ratio of 2:1. The results showed that the ethanol-acetaldehyde conversion rate was above 60%, and the butadiene selectivity was ≥60%, and the continuous operation was at least 153 hours.
[0189] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A ZrO x -A method for preparing a Beta catalyst, characterized in that: The method includes: (1) acid washing and dealuminization of H-Beta molecular sieve to obtain Si-Beta molecular sieve; (2) mixing Si-Beta molecular sieve, template and water, and then performing crystallization treatment to obtain the Recry-Beta molecular sieve; (3) In the presence of a precipitant, Zr is loaded onto the Recry-Beta molecular sieve, and then dried and calcined to obtain the ZrO x -Beta catalyst; Wherein, the particle size of the H-Beta molecular sieve is less than 90 nm; Wherein, the molar ratio of the template agent to the Si-Beta molecular sieve calculated as SiO2 is 0.08-0.25; The load conditions include: temperature of 60-140°C and positive pressure; The amount of the sedimentation agent used is such that the pH of the material after loading is greater than 7 and less than 13.
2. The method according to claim 1, wherein: The particle size of the H-Beta molecular sieve is 20-50 nm.
3. The method according to claim 1 or 2, wherein: In step (1), the conditions for acid washing and aluminum removal are such that the content of silicon dioxide in the obtained Si-Beta molecular sieve is greater than 99.5 wt %; Preferably, the crystallinity of the Si-Beta molecular sieve is 60-90%, more preferably 70-85%; Preferably, the BET specific surface area S of the Si-Beta molecular sieve is BET 450-680m 2 / g, more preferably 480-650m 2 / g; Preferably, the total pore volume V of the Si-Beta molecular sieve is 总 0.25-0.85cm 3 / g, more preferably 0.45-0.7cm 3 / g; Preferably, the stacking pore volume V of the Si-Beta molecular sieve is meso 0.2-0.55cm 3 / g, more preferably 0.26-0.48cm 3 / g.
4. The method according to any one of claims 1 to 3, wherein: The template has at least one of the structures shown in formula (1): Wherein, R1, R2, R3 and R4 are each independently selected from an alkyl group having 1 to 4 carbon atoms, preferably, R1, R2, R3 and R4 are each independently selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl, more preferably methyl or ethyl; X - including hydroxide ions or halogen anions; Preferably, the template is tetramethylammonium hydroxide and / or tetraethylammonium hydroxide; Preferably, the molar ratio of the template to the Si-Beta molecular sieve calculated as SiO2 is 0.1-0.2; Preferably, the molar ratio of water to Si-Beta molecular sieve calculated as SiO2 is 3-10, more preferably 5-8.
5. The method according to any one of claims 1 to 4, wherein: In step (2), the crystallization conditions include: a crystallization temperature of 100-300° C., preferably 110-150° C.; a crystallization time of 12 h-120 h, preferably 24 h-72 h; Preferably, the method further comprises: calcining the crystallized product to obtain the Recry-Beta molecular sieve; Preferably, the calcination conditions include: a calcination temperature of 400-650° C., more preferably 500-600° C.; and a calcination time of 2-8 h, more preferably 3 h-5 h.
6. The method according to any one of claims 1 to 5, wherein: In step (3), the loading method includes: impregnating the Recry-Beta molecular sieve with a Zr precursor solution; Preferably, the amount of each component used is such that, based on the total weight of the catalyst, the content of Recry-Beta molecular sieve is 95-99.9wt%, more preferably 97-99.5wt%, and the content of zirconium-containing species calculated as Zr oxide is 0.1-5wt%, more preferably 0.5-3wt%.
7. The method according to any one of claims 1 to 6, wherein: In step (3), the load conditions include: temperature of 80-120°C; pressure of 0.2MPa-0.8MPa; and / or The loading time is 4-68h, preferably 10-50h; and / or The calcination conditions include: temperature of 400-600° C. and time of 1-6 hours.
8. The method according to any one of claims 1 to 6, wherein: In step (3), the amount of the sedimentation agent is such that the pH of the material after loading is 8-12; and / or The sedimentation agent is selected from at least one of urea, ammonia and ammonium salt.
9. ZrO prepared by the method according to any one of claims 1 to 8 x -Beta catalyst; Preferably, the zirconium-containing species in the catalyst is a monoclinic / tetragonal mixed phase, wherein: The monoclinic phase accounts for more than 50% of the zirconium-containing species, and more preferably 55-80%.
10. ZrO according to claim 9 x -Beta catalyst, wherein The catalyst has a silicon to aluminum ratio of 800 or more, more preferably 1200-2500; and / or The total acid content of the catalyst is 220-400 μmol / g, preferably 250-350 μmol / g; and / or In the catalyst, the ratio of weak acid to medium strong acid is 2-7, preferably 3.5-6.5; and / or The BET specific surface area S of the catalyst BET 150-550m 2 / g, preferably 330-510m 2 / g; and / or The total pore volume V of the catalyst 总 0.45-0.7cm 3 / g, preferably 0.55-0.67cm 3 / g; and / or The catalyst has a bulk pore volume V meso 0.3-0.7cm 3 / g, preferably 0.4-0.55cm 3 / g; and / or The average particle size of the catalyst is 20-50 nm, preferably 20-30 nm; Preferably, based on the total weight of the catalyst, the content of Recry-Beta molecular sieve is 95-99.9wt%, more preferably 97-99.5wt%, and the content of zirconium-containing species calculated as Zr oxide is 0.1-5wt%, more preferably 0.5-3wt%.
11. A ZrO x -Beta catalyst, characterized in that The catalyst comprises a Beta molecular sieve and a zirconium-containing species supported on the Beta molecular sieve, wherein the zirconium-containing species is a monoclinic / tetragonal mixed phase; Wherein, the monoclinic phase accounts for 50%-80% of the zirconium-containing species; Wherein, the crystallinity of the catalyst is 30-60%; Preferably, the silicon to aluminum ratio of the catalyst is 1200-2500; The total acid amount of the catalyst is 250-350 μmol / g; and / or In the catalyst, the ratio of weak acid to medium strong acid is 3.5-6.5; and / or The BET specific surface area S of the catalyst BET 330-510m 2 / g; and / or The total pore volume V of the catalyst 总 0.55-0.67cm 3 / g; and / or The catalyst has a bulk pore volume V meso 0.45-0.55cm 3 / g; and / or The average particle size of the catalyst is 20-30 nm; Preferably, based on the total weight of the catalyst, the content of Recry-Beta molecular sieve is 95-99.9wt%, more preferably 97-99.5wt%, and the content of zirconium-containing species calculated as Zr oxide is 0.1-5wt%, more preferably 0.5-3wt%.
12. ZrO according to any one of claims 9 to 11 x -Beta catalyst is used in hydrocarbon conversion reaction, preferably in the reaction of preparing 1,3-butadiene from ethanol-acetaldehyde.
Citation Information
Patent Citations
Modified beta zeolite and catalytic cracking catalyst, and preparation methods and applications thereof
CN113582193A
Zirconium-containing catalyst, preparation method and application thereof, and method for preparing butadiene from ethanol and acetaldehyde
CN116020431A
Prepn of n-heptane hydroisomerizing catalyst
CN1772385A
Composition based on cerium, zirconium and tungsten, preparation process and use in catalysis
US20130164201A1
Catalytic cracking catalyst and process for preparing the same
US20230249165A1